The power of the Buddhas: the politics of Buddhism during the Koryŏ dynasty (918-1392) - Vermeersch, Sem (Harvard East Asian monographs, 2008)
Introduction -- Buddhism and the state in late Silla -- Foundations of a new Buddhist policy: T'aejo and Buddhism -- Legal provisions on the status of monks -- The Saṅgha examination, ranking and administration -- The royal and state preceptors -- The Buddhist temple economy in early Koryǒ -- Buddhist state rituals